Analyzing the elements related to parking demand: An empirical study in Beijing. (21st April 2016) - Yao, Guangzheng; Guo, Hongwei; Li, Chunyan; Sun, Hairui
Previous studies have shown that constraining parking policy can alleviate air pollution and traffic congestion by reducing vehicle ownership and usage. The feasibility and efficiency of the parking policy are crucial to urban traffic planning and management. With the aim of exploring the elements related to parking demand and improving the policy efficiency, this study analyzed several factors relevant to vehicle ownership and usage which may affect the feasibility of policy. In all, 40, 000 samples obtained from Beijing residents' trip interview survey were used. A combined method with empirical study and network dynamic analysis is used to give a clear relationship between parking supply and private usage. The results, after conducting a quantitative analysis, show that vehicle ownership is related to family income, family size, geographic location, and parking fee, while trip purpose and parking fee in destination influence the frequency of car usage. It is noteworthy that the proportion of free parking in working trips is up to 96%, and single driving occupies a proportion as high as 90%. The research suggests that planners should be cautious of parking facility supply strategy and pay great attention to parking fees of working trip.